2010
DOI: 10.1590/s1808-86942010000100004
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da relação entre severidade do zumbido e perda auditiva, sexo e idade do paciente

Abstract: Ti nnitus is a symptom present in approximately 15% of the world population. Most patients are between 40 and 80 years of age; the prevalence above 60 reaches 33%. About 20% have moderate to severe impact in the quality of life but the factors associated with the tinnitus annoyance are not completely known. Aim: The objective of this study is to evaluate the relationship between age, gender and hearing loss on tinnitus annoyance. Materials and methods: 68 patients were evaluated at the tinnitus center at our h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
41
1
25

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 29 publications
8
41
1
25
Order By: Relevance
“…So 59.3% of the sample interviewed reported tinnitus corroborating with this study 31 . The average score on the THI of the sample was 26.94, which disagreed with other 32 .…”
Section: Discussioncontrasting
confidence: 79%
“…So 59.3% of the sample interviewed reported tinnitus corroborating with this study 31 . The average score on the THI of the sample was 26.94, which disagreed with other 32 .…”
Section: Discussioncontrasting
confidence: 79%
“…Regarding the incidence of tinnitus according to sex, there is no consensus in the literature. There are studies that showed a slight increase in the number of female subjects, justified by the greater availability and concern to seek medical assistance (20,21,22) ; however, other studies have suggested a prevalence in males due to excessive exposure to noise (23,24) , agreeing with the findings of this research.…”
Section: Discussionsupporting
confidence: 88%
“…The symptom was observed in 22% of the sample, with a higher prevalence in females, increasing significantly with age, producing severe discomfort in 34% of the group (6) . It can be said that tinnitus is commonly associated with acoustic trauma, ear disease, head and neck trauma, cardiovascular, metabolic, neurological, psychiatric disorders, dental factors, side effects of ototoxic drugs, caffeine abuse, nicotine and alcohol (5,7) . It is also associated with hearing loss, and 78% to 90% of patients with tinnitus have changes in audiometric thresholds (7) .…”
Section: Introductionmentioning
confidence: 99%
“…It can be said that tinnitus is commonly associated with acoustic trauma, ear disease, head and neck trauma, cardiovascular, metabolic, neurological, psychiatric disorders, dental factors, side effects of ototoxic drugs, caffeine abuse, nicotine and alcohol (5,7) . It is also associated with hearing loss, and 78% to 90% of patients with tinnitus have changes in audiometric thresholds (7) . The questionnaire called the Tinnitus Handicap Inventory (THI) evaluates the emotional, functional and catastrophic tinnitus aspects and has been broadly used in the clinical setting to assess patients with this symptom for the quantification of nuisance and analysis of responses to proposed treatments (8) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation